Evaluation Of The Effectiveness And Complication Profile In The Treatment Of Stones Up To 1.5 Cm In The Renal Pelvis: Remote Shock Wave Lithotripsy, Retrograde Intrarenal Surgery And Percutaneous Nephrolithopaxy - Magomedovna, Akaeva Maryam; Magomed-Kamilovich, Gamzatov Zalimkhan; Magomedovna, Azizova Paizanat; Tagirovna, Zairbekova Milana; Musaevna, Manatova Patimat; Muminovna, Akhmedova Alina; Muminovna, Akhmedova Aida; Germanovna, Aslanova Amina; Magomedovna, Khalidova Patimat; Shamilevna, Kurbaiilova Shahruzat (Journal of Neonatal Surgery, 2025)
The aim of the study was to conduct a comparative analysis of the effectiveness and frequency of complications in the treatment of renal nodules up to 1.5 cm in the renal pelvis using three methods: remote shock wave lithotripsy (RVL), retrograde intrarenal surgery (RIR) and percutaneous nephrolithopaxy (PCN). The study included 150 patients evenly divided into three groups, depending on the treatment method used. The clinical efficacy (stone-free rate), the frequency of repeated interventions, the complication profile (according to the Clavien-Dindo scale), the duration of hospitalization and the overall recovery of the patient were evaluated. The highest rate of complete stone removal (SFR) was recorded in the PKN group (96%), while the incidence of complications was moderate. RIRX provided a high level of efficiency (90%) with minimal invasiveness. DVL showed the lowest effectiveness (66%) and the highest risk of repeated procedures, however, it was characterized by the shortest period of hospitalization. All three methods have clinical significance in the treatment of renal pelvis stones up to 1.5 cm, however, the choice of optimal tactics should be based on the characteristics of the stone, the anatomical features of the patient and the resource capabilities of the institution. RIRX and PKN demonstrate higher efficiency compared to DVL with a comparable safety profile.